Estimated Glomerular Filtration Rate (eGFR) as a Predictor of 1-Month Clinical Outcome in First-Ever Acute Ischemic Stroke Patients - Billi; Akbar, Muhammad; David Gunawan Umbas; Hamid, Firdaus; Bintang, Andi Kurnia; Lotisna, Mimi (CoinReads Media Prima, 2023)
Introduction: Renal dysfunction is a new risk factor that is thought to influence the clinical outcome of acute ischemic stroke. In this case, the estimated glomerular filtration rate (eGFR) value is used as an approach to assess kidney function status in acute ischemic stroke patients. This study aims to find the relationship between eGFR and clinical outcomes of acute ischemic stroke. Method: 70 samples were obtained according to inclusion criteria. eGFR is calculated within first week of stroke onset using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formula. A normality test was carried out on the data, then determined the correlation and compared eGFR with good [modified Rankin Scale (mRS) 0-2] and poor (mRS 3-6) clinical outcomes on the 30th day. Results: In this study, the average age of the sample was 61.37 years. The largest population was in the 45-59 mL/min/1.73 m2 eGFR group (38,6%). The mean eGFR (p<0.001) for all samples, good, and bad outcome groups was respectively 59.90 ± 21.09, 79.79 ± 19.21, and 52.49 ± 16.57. In this study the poor outcome group had a lower mean eGFR than the good outcome group (52.49 mL/min/1.73 m2 vs 79.79 mL/min/1.73 m2), with a cut-off value of 62 mL/min/1.73 m2 (sensitivity 80.39%, specificity 84.21%) tended to have worse clinical outcomes. Conclusion: Based on the results of this study, eGFR has a relationship with clinical outcomes (p<0.001) and can objectively predict clinical outcomes on the 30th day of acute ischemic stroke.